Photography: Science, Technology, and Practice in Nineteenth-Century Canada - Schwartz, Joan (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 2022)
Drawing upon empirical research from a larger project on photography in nineteenth-century British North America, this essay proceeds from the conviction that photography—as science, as technology, as practice—warrants closer scrutiny for the ways in which it contributed to the creation and circulation of knowledge in mid-to-late nineteenth-century Canada. Based on surviving images as well as those known only from the written record, this foray into the entwined histories of photography, science, and technology, while far from comprehensive, is intended to open up new directions for further study by historians of science and technology.